Anterior to Midposterior Corpus Callosum Subregions Are Volumetrically Reduced in Male Alcoholics but Only the Anterior Segment Is Associated to Alcohol Use - de Souza, Rodrigo Stênio Moll; Rosa Jr., Marcos; Escobar, Thayssa Dalla Costa; Gasparetto, Emerson Leandro; Nakamura-Palacios, Ester Miyuki (Frontiers in Psychiatry, 2019)
Alcohol consumption seems to affect corpus callosum morphometry irrespectively of an alcohol use disorder (AUD) diagnosis. The present study examined the relationship between corpus callosum (CC) subregion volumes and alcohol use patterns in AUD and non-AUD subjects. Twenty-two male AUD patients and 23 healthy matched non-AUD subjects were recruited from March 2016 to July 2017. Volumetric data were acquired through Magnetic Resonance and analyzed by the FreeSurfer software. AUD subjects were in abstinence for 45.1 days ± 36.8 (SD), consumed higher amounts of alcohol and presented higher AUDIT scores than controls (p < 0.0001). A multivariate analysis corrected by age and tobacco use indicated that AUD patients presented smaller CC volumes compared to non-AUD subjects (p < 0.01), except for the posterior subregion. A multiple regression analysis corrected by age and tobacco use including CC volumes from all subjects and the amount of daily alcohol ingestion as variables indicated that anterior CC volume was negatively (p < 0.001) associated to alcohol consumption. This study demonstrated that CC subregions were smaller in AUD subjects, as expected, and that the volume of the anterior segment was inversely associated to increasing daily amounts of alcohol, indicating greater frontal region vulnerability to harmful alcohol effects.